a)
* Xét $ \Delta MBE$ và $\Delta AEC$:
$\widehat{MEB}=\widehat{AEC}$ $(đđ)$
$\widehat{MBE}=\widehat{EAC}=(60^o)$
$=> \Delta MBE \sim \Delta CAE (g.g)$
$=> \dfrac{BE}{AE}=\dfrac{ME}{CE}= \dfrac{MB}{AC}$
$=> \dfrac{MB}{AC} = \dfrac{AM}{CN}$ $(BM=AM; AC=AN)$
* Xét $ \Delta ABF$ và $\Delta CFN$:
$\widehat{AFB}=\widehat{CFN}$ $(đđ)$
$\widehat{BAF}=\widehat{NCF}=(60^o)$
$=> \Delta ABF \sim \Delta CNF (g.g)$
$=> \dfrac{AF}{CF}= \dfrac{AB}{CN} = \dfrac{AM}{CN} (AM=AB)$
$=> \dfrac{ME}{CE}= \dfrac{AF}{CF}(= \dfrac{AM}{CN})$
$=> EF//AM$ (Ta-lét đảo)
$=> \widehat{CFE}=\widehat{CAM}=120^o$ $( \widehat{CAM} = \widehat{CAB} + \widehat{BAM} = 60^o + 60^o = 120^o ) $
$=> \widehat{AFE}=60^o$ ($ \widehat{AFE}$ kề bù $ \widehat{EFC}$)
Mà $\widehat{FAE}=60^o$ (gt)
=> $\Delta AEF$ đều.
b)
Ta có:
$\dfrac{BE}{AE}=\dfrac{AF}{CF}(=\dfrac{ME}{CE})$
$=> AE.AF=BE.CF$
$<=> AE^2=4.9=6^2 (AE=AF)$
$<=> AE=EF=6 (cm)$
Vậy $EF=6cm$
Last edited by a moderator: 18 Tháng năm 2013